Comparison between total intravenous anesthesia and balanced anesthesia on postoperative opioid consumption in patients who underwent laparoscopic-assisted distal gastrectomy. Issue 19 (May 2020) - Kim, Doo-Hwan; Yun, Hye Joo; Park, Sooin; Leem, Jeong-Gil; Karm, Myong-Hwan; Choi, Seong-Soo
Abstract : Abstract: Remifentanil is the most frequently prescribed opioid for total intravenous anesthesia (TIVA) or balanced anesthesia (BA), due to its favorable pharmacological properties. However, several studies have reported opioid-induced hyperalgesia and/or acute tolerance after intraoperatively using remifentanil. In addition, it is imperative to control postoperative pain with lower doses of opioid anesthetic agents. Therefore, we compared the amount of opioid consumption between TIVA with propofol-remifentanil and BA with desflurane-remifentanil, to control postoperative pain in patients who underwent laparoscopic-assisted distal gastrectomy (LADG) with gastroduodenostomy. We retrospectively evaluated demographic variables (age, gender, height, weight, and smoking habits), the duration of general anesthesia (GA), and intraoperatively administered remifentanil consumption through the electronic medical records of patients who underwent LADG with gastroduodenostomy due to early stomach cancer. The primary outcome was postoperative opioid consumption during postoperative day (POD) 2. The secondary outcomes were the incidence of any rescue opioid analgesics administered, numeric rating scale, and various adverse effects during POD 2. We categorized the data in 2 patient groups to compare TIVA with propofol-remifentanil (TIVA group) to BA with desflurane-remifentanil (BA group) on the postoperative opioid analgesic consumption. We divided 114 patients into the TIVA (46 patients) and BA (68 patients) groups. Opioid consumption as a primary outcome was significantly higher in the BA group than in the TIVA group during POD 2 except in the post-anesthesia care unit. The cumulative opioid consumption was significantly higher in the BA than in the TIVA group. The incidence of rescue analgesic at POD 2 was higher in the BA than in the TIVA group. In the TIVA group, remifentanil consumption was higher, and the duration of GA was shorter than that in the BA group. No statistically significant differences were observed when comparing other variables. Our results indicated that the maintenance of GA with TIVA (propofol-remifentanil) reduces opioid consumption for postoperative pain control compared to BA (desflurane-remifentanil) in patients undergoing LADG with gastroduodenostomy.